CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DALAM DUNIA DIGITAL MELALUI SISTEM E-COMMERCE - Jam'an (Globalwriting Academica Consulting & Publishing, 2021)
Advances in technology have caused a lot of changes that occur in various human lives, including shopping activities. Through the presence of the internet, shopping activities now no longer need to be done traditionally, but can be carried out by utilizing existing e-commerce. The existence of e-commerce makes various companies need to adjust their Customer Relationship Management (CRM) business strategies. This is because there will be many changes that occur in CRM when they are in an e-commerce environment. This research was carried out using a qualitative approach with data sources derived from previous studies. The results show that there are changes that occur in CRM when in an e-commerce environment. Then this research also finds out how the characteristics of CRM while in the e-commerce environment.